Basic Psychological Needs, Physical Self-Concept, and Physical Activity Among Adolescents: Autonomy in Focus - Fraguela-Vale, Raúl; Varela-Garrote, Lara; Carretero-García, Miriam; Peralbo-Rubio, Eva María (Frontiers in Psychology, 2020)
The contribution of this research lies in its dual approach to the question of physical activity among adolescents, combining objective measurement of physical activity by teenagers and a comparison of psychological satisfaction through physical activities involving differing degrees of autonomy (i.e. organized or unstructured). Using the conceptual framework of Self-Determination Theory, the analysis also examines the relationship between levels of physical activity among adolescents and physical self-concept and satisfaction of basic psychological needs during exercise. The study surveyed 129 first-year higher secondary education students from schools in the city of A Coruña. Satisfaction of basic psychological needs during organized and unstructured physical activities was measured using an AF5 Multidimensional Self-Concept Scale questionnaire. Physical activity levels were assessed based on step count per day for a week as measured by an accelerometer. The results show that the daily step average recorded by students (7400) is below the minimum recommended levels of physical activity for this age group, that students are more active on weekdays than at the weekend, and that there is no significant difference in physical activity levels between male and female subjects. Findings from the comparative analysis of the three basic psychological needs show greater satisfaction of the need for autonomy during unstructured activities, and greater satisfaction of the need for competence during organized activities. No variation in terms of sex was found in relation to satisfaction of the need for autonomy or relatedness from unstructured activities; however, girls showed notably lower satisfaction than boys in relation to the need for competence. Self-esteem was found to play an important mediating role and observed to be strongly related to sex. Organized physical activity was found to provide greater need satisfaction among boys than girls across all categories. The study showed no relationship between psychological variables and objectively measured physical activity. Basic psychological needs show significant positive interrelation between them and a significant positive relationship between them and physical self-concept, as expected based on previous literature; however, no corresponding correlation is observed with the different levels of physical activity recorded in the study.